Building a Geometallurgical Model for Early-Stage Project Development – A Case Study from the Canahuire Epithermal Au-Cu-Ag Deposit, Southern Peru - R Baumgartner (The Australasian Institute of Mining and Metallurgy, 2011)
The Canahuire deposit is a recently discovered Au-Cu-Ag epithermal deposit in Southern Peru. A geometallurgy program is a key study element of the project Feasibility study. Metallurgical, mineralogical, and comminution studies have been completed over a suite of samples, spatially distributed among the various geological/ore domains. The early stage of Canahuire presents challenges as there is a lack of metallurgical information to guide geometallurgical sampling, in contrast with an established deposit at a more advanced stage of development or mining. Nevertheless, the available information will assist in the development of geometallurgical domains for Canahuire in order to ensure that future metallurgical, mineralogical, and comminution test work is representative of the deposit variability. This supplementary knowledge will be able to predict important metallurgical parameters which will be incorporated into a geometallurgical model to spatial predict material types, metallurgical recovery and through put. The information obtained will be a valuable addition to the future mine plan, influencing process design, engineering design, plant operation, operating and capital costs, and ultimately will reduce project development risk.